Never too young for a salivary gland carcinoma ex-pleomorphic adenoma - Ahmad Muizzuddin Ahmad Fuad; Lum Sai Guan; Mohd Razif Mohamad Yunus (The Egyptian Journal of Otolaryngology, 2024)
Abstract Background Carcinoma ex-pleomorphic adenoma (CXPA) can either arise primarily as a de novo or from the malignant transformation of a benign pleomorphic adenoma (PA). CXPA mostly occurs in adults aged 50 to 70 years; hence, the occurrence of CXPA in younger ages is not common. Case presentation We report a 27-year-old female who had a history of submandibulectomy for pleomorphic adenoma, and presented with recurrent left submandibular swelling for 4 months. The mass was rapidly increasing in size and was associated with occasional throbbing pain. Examination showed a multilobulated, firm left submandibular swelling with no overlying skin changes. FNAC was performed twice, by conventional and ultrasound-guided techniques, and both concluded as benign salivary gland tumours. CT scan and MRI revealed a well-demarcated tumour with an area of necrosis within, with no obvious invasion into surrounding soft tissue and no significant lymphadenopathy. Having high suspicion of a malignant transformation, the tumour was resected with a concurrent modified radical neck dissection. The histopathological examination confirmed a carcinoma ex-pleomorphic adenoma with the myoepithelial malignant component. The patient subsequently received adjuvant radiotherapy. This case demonstrated that CXPA, although rare, can occur in young adults. Pre-operative FNAC and radiological imaging may mimic a pleomorphic adenoma. Conclusion The presence of recurrent tumours with rapid growth should alarm the clinician about a possible malignant transformation of a benign parotid tumour.